A Prospective Observational Study on Polypharmacy in Geriatrics at A Private Corporate Hospital - Viswam K. Subeesh, Nair Gouri, Elsa Thomas Beulah, Velu Shivashankar (Journal of Applied Pharmaceutical Science, 2017)
Background: Geriatrics are the rapidly growing age group suffering with two or more chronic diseases leading to polypharmacy. Polypharmacy can boost the risk of adverse events, drug interactions and medication no adherence. This study aims at investigating the prevalence, different factors and consequences associated with polypharmacy in geriatrics. Methodology: A prospective observational study was carried out for a duration of nine month in a private corporate hospital, Coimbatore, Tamil Nadu. Patients above 65 years were included in the study. The collected data was investigated for polypharmacy and analyzed for factors and consequences associated with polypharmacy. Results: A total of 344 patients were included in the study. The average age of the study population was found to be 72.9 ± 6.5. Average hospital stay of the study population was found to be 10.22±8.7 days. A total of 2034 drugs were prescribed for the study population. The average number of drugs prescribed for the study population was found to be 9.68 (±1.94) with minimum of 5 drugs to the maximum of 14 drugs during the study period, 110 (52%) among the study population were found to be prescribed with potentially inappropriate medications. The mean value of drug related problems in the study population was found to be 1.81±1.3. Conclusion: The prevalence of polypharmacy and potentially inappropriate medications use were very high among the study population. This study assured the need of close monitoring of patients under polypharmacy since it can lead to higher number of drug related problems and increased hospital stay.
Keywords: Polypharmacy, Geriatrics, Multiple Comorbidities, Potentially inappropriate medications.